PENGARUH MEGALITIK DI SITUS-SITUS PERTAHANAN TRADISIONAL MASA KOLONIAL AWAL DI MALUKU - Mansyur, Syahruddin (BRIN, 2016)
This study was conducted at three sites; Bukit Amaiha, Bukit Wawani, and Bukit Kapahaha. These sites had correlation in settlement, traditional defense and megalithic sites. The result shows that the dolmen is a product of megalithic culture found on traditional defense sites on the island of Ambon. The influence on megalithic culture on traditional defense sites caused by the strong megaliths concept in the early colonial period in Maluku. Megalithic concept in Bukit largest Amaiha related to people effort to maintain the social status of their leader. On the other hand, it also related to their effort to gain cosmological legitimacy between leaders and community at Bukit Wawani.